LITERATUR REVIEW: PENGEMBANGAN SUMBER DAYA MANUSIA MELALUI PEMBINAAN KARIR - Kuncahyo, Rendy Dwi; Ramadhani, Syahrur; Wibawa, Putra Ramadhan (Pusat Penelitian dan Pengabdian (P3M) STKIP Majenang, 2025)
Human resource (HR) development is a key element in improving organizational competitiveness, especially through a structured career development approach. This study aims to examine the role of career development in HR development based on a systematic review of literature from various sectors. The method used is a systematic literature review with thematic analysis and qualitative synthesis of 15 scientific articles from various international databases such as ResearchGate, Elsevier, and Emerald Insight. The results of the study indicate that competency development, the role of information technology, inclusive organizational policies, and external factors such as government policies are determining factors in the effectiveness of career development. The findings also indicate a direct relationship between effective career development programs and increased employee performance and loyalty. However, this study also identified limitations such as a dominant focus on the formal sector and certain country contexts, as well as limited access to technology and training. Therefore, this study recommends the need for inclusive career development policies, increased access to technology, and further research in the informal sector and local contexts. This study is expected to be the basis for formulating adaptive career development strategies that have a direct impact on strengthening HR in various organizations